Diagnostic and prognostic significance of detecting mutations in the BRAF, TERT, RAS, RET/PTC, PAX8/PPARG in the material of fine needle aspiration biopsy thyroid nodules in the IV cytological group (Bethesda, 2017) - A. A. Musaelyan; S. V. Lapin; V. D. Nazarov; E. S. Kozorezova; S. L. Vorobyev; S. V. Orlov (Опухоли головы и шеи, 2022)
Introduction. Fine needle aspiration biopsy followed by cytological examination is the gold standard in the diagnosis of thyroid nodules. However, up to one third of cases represent an indeterminate result (Bethesda Thyroid Classification, 2017) III—V). Among such cases, category IV is the most common and most difficult to interpret (Bethesda, 2017). The study objective is to determination of the diagnostic and prognostic significance of the molecular genetic study of the fine needle aspiration biopsy material in patients with thyroid nodules with the cytological category Bethesda, IV.Materials and methods. The study included surgical thyroid samples obtained from patients whose cytological examination revealed pathology of cytological category IV according to the Bethesda classification (2017). group 1 included surgical samples from 143 patients with thyroid lesions, and group 2 - cytological material from 45 patients. Determination of the BRAF V600E mutation, mutations in the RAS genes (KRAS, HRAS, NRAS) was carried out using allele-specific polymerase chain reaction, and the RET / PTC1, RET / PTC3 and PAX8 / PPARG translocations were determined using reverse transcription polymerase chain reaction. Sanger sequencing was used to detect mutations in the promoter region of the TERT gene.Results. In group 1, an overall prevalence of the studied mutations in thyroid cancer was 35.1 %: 8.8 % of cases were mutation BRAF V600E, 24.6 % - mutations in the RAS genes, 1.8 % - mutation C228T in the TERT gene. The C228T mutation in the TERT gene was found in 1 case of widely invasive Hurtle cell carcinoma. The prevalence of mutations in benign formations was 4.7 %. mutations in RAS genes were also found in them in group 1, mutation BRAF V600E was associated with the presence of extrathyroid invasion (p = 0.024), vascular invasion (p = 0.018), and lymph node metastases (p = 0.018). In group 2, using the genetic panel sensitivity and specificity were equal: 36.4 and 93.9 %, respectively. positive and negative predictive values were 66.7 and 81.6 %, respectively. No RET / PTC and PAX8 / PPARG translocations were found in groups 1 and 2.Conclusion. The investigated molecular genetic panel, having a high specificity for carcinomas, will make it possible to supplement the cytological diagnostics of material in the category Bethesda, IV. BRAF V600E was associated with an aggressive morphological pattern.